Carnival in Trinidad - Norton, Noel (Bon Genie Ltd., Port of Spain, Trinidad, 2009)
Description on the back of postcard: For two days non stop excitement Trinidad erupts into this annual carnival. Here revellers group in Port of Spain’s Savannah.” Postcard numbered BG 5.
Colour: Coloured; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Carnival--Trinidad and Tobago; Carnival costume--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Women--Trinidad and Tobago; Queen's Park Savannah